1985
DOI: 10.2190/4ma2-dcgk-44hw-7qud
|View full text |Cite
|
Sign up to set email alerts
|

System-Assigned Strategies and CBI

Abstract: Presents a theoretical framework for designing computer-based systems that guide students in the selection of learning strategies. Reviews the relationship between learning strategies and instructional strategies. Compares theories for determining when system-assigned learning strategies will promote acquisition of knowledge and skills. Discusses task-relevant aptitude as a factor in the assignment of learning strategies. Describes advantages of learning strategies as stimuli to effective cognitive processing;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Learner control may be unsuccessful for some subjects because they lack metacognitive skills (Allen & Merrill, 1985;Rigney, 1978) or lack information they need about the learning progress to make meaningful decisions about how to manage learning (Tennyson & Rothen, 1979). Holden (1995) found that higher self-directed learning readiness participates had higher achievement than lower level participants and lower level self-directed learning readiness participates with program control had higher achievement than participants with learner control.…”
Section: Self-directedness and Cbi Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Learner control may be unsuccessful for some subjects because they lack metacognitive skills (Allen & Merrill, 1985;Rigney, 1978) or lack information they need about the learning progress to make meaningful decisions about how to manage learning (Tennyson & Rothen, 1979). Holden (1995) found that higher self-directed learning readiness participates had higher achievement than lower level participants and lower level self-directed learning readiness participates with program control had higher achievement than participants with learner control.…”
Section: Self-directedness and Cbi Designmentioning
confidence: 99%
“…For some subjects, learner control may be unsuccessful because they lack the metacognitive skills (Allen & Merrill, 1985;Rigney, 1978) or lack the information they need about their learning progress to make meaningful decisions about how to manage learning (Tennyson & Rothen, 1979). Motivation, as well as cognition, influences learner control (Steinberg, 1991).…”
Section: Self-directedness and Cbi Designmentioning
confidence: 99%
See 1 more Smart Citation
“…If CBI's instructional impact was not found for the learner control issue, it might then be discovered by examining the cognitive differences literature. Many reports (Allen & Merrill, 1985;Bangert-Drowns et al, 1985;Farr, 1985;Gray et al, 1985;Neimiec & Walberg, 1985;and Zemke, 1984) have suggested that the main reason for selecting a CBI system is to better deal with differences in cognitive abilities and styles.…”
Section: Cognitive Differencesmentioning
confidence: 99%
“…Smart technology can also be used for accommodating students with different cognitive abilities (Allen & Merrill, 1985;and Gray et al, 1985). Smart technology programs involve interactions between students and the computer so that the type of feedback and instructional materials provided fit the students' level of knowledge (Gray et al).…”
Section: Cognitive Differencesmentioning
confidence: 99%